International Transport Infrastructure and Regional Economic Development - Karsten Mau; Mingzhi (Jimmy) Xu; Yawen Zheng (CESifo GmbH, 2025)
We evaluate how access to international transport infrastructure promotes trade and economic development. Exploiting the gradual unfolding of transcontinental rail freight connections between China and Europe, our empirical findings indicate increasing exports from connected cities, with positive spillovers to neighboring cities and other indicators economic activity. Not all products and cities are equally responsive to new rail export opportunities. We set up a multi-sector heterogeneous firms model with a rich specification of trade costs, in which firms optimize trade costs by choosing alternative transportation modes and routes. Leveraging a unique data set on trade flows between Chinese cities, we calibrate our model to discuss local welfare effects, relying on sufficient statistics that quantify changes in city-level trade costs. We also highlight significant spatial distributional effects of trade infrastructure development.
Keywords: F14; F15; R11; R41; 330; transport infrastructure; trade; regional development; China